Nanoparticle forming polyelectrolyte complexes derived from well-defined block copolymers. (8th May 2023) - Bakhtiari, Sara E.; Joubert, Fanny; Pasparakis, George; Brocchini, Steve; Williams, Gareth R.
Graphical abstract: Highlights: Narrow molecular weight poly(methacrylic acid) and block co-polymers synthesized. These self-assembled into small, monodisperse, polyelectrolyte complexes (PECs). The PECs are highly haemocompatible, and can be loaded with a drug cargo. The PECs are responsive to temperature and pH. Abstract: Polymers can be used in nanoparticle associated formulations to encapsulate cytotoxic drugs (e.g., paclitaxel). Polyelectrolyte complexes (PECs) that form drug associated colloids also have potential to form particulate associated formulations. We used RAFT polymerisation to prepare small families of narrow molecular weight distributed (i) methacrylate block co-polymers comprised of oligomeric ethylene glycol, poly(ethylene glycol) methyl ether methacrylate (PEGMA), and dimethyl amino pendent chains, 2-(dimethylamino) ethyl methacrylate (DMAEMA), and (ii) poly(methacrylic acid), PMAA. These polymers were examined for their ability to form PECs capable of drug encapsulation. Optimal control in RAFT polymerisation was confirmed by the linear increase of molecular weight and the narrow dispersity of the polymers (<1.2) as determined by 1 H nuclear magnetic resonance and gel permeation chromatography. Dynamic light scattering and transmission electron microscopy showed formation of well-defined monodispersed nanoparticles with a hydrodynamic diameter of 25 ± 3 nm upon self-assembly of poly(PEGMA0.23 -b-DMAEMA0.77 )99 and PMAA75 . These PECs are highly haemocompatible. Thin film hydration was used to encapsulate two hydrophobic drugs, paclitaxel and carmofur, into spherical nanoparticles. The results show that carmofur was encapsulated markedly more effectively than paclitaxel (72 vs 1.5%).